Body Image Perception Among Multi-Ethnic Male University Students (Jurnal Kemanusiaan, 2017)
The present study aimed to investigate student self-rating towards body dissatisfaction, drive for muscularity and self-esteem, as well as to investigate their relationship. Results from a sample of 293 male students from University Malaysia Sabah showed a significant positive relationship between body dissatisfaction and drive for muscularity (r = .22, p < .01). An interesting result was that body dissatisfaction is positively correlated with higher self-esteem (r = .142, p